Examining the Global Competence and TPACK Development Model for Prospective Teachers in Accounting Economics - Kardiyem, Kardiyem; Kusmuriyanto, Kusmuriyanto; Aeni, Ida Nur; Susilowati, Nurdian (FKIP Universitas Lampung, 2022)
The Development Model of Technological, Pedagogical, and Content Knowledge (TPACK) and Global Competency of Prospective Teachers in Accounting Economics. Objectives: This research examines the development model of global competency and technological, pedagogical, and content knowledge (TPACK) of prospective teachers in accounting economics. Methods: Design of this research using clausal associative design. The respondents of the study were 91 students of accounting education at Universitas Negeri Semarang. Findings: Analysis results using WarpPLS 6.0. shows that socioeconomic status did not affect technological, pedagogical, and content knowledge (TPACK) and global competence. In addition, there is a direct effect of student engagement and student perception of teaching methods on technological, pedagogical, and content knowledge (TPACK) and global competence. The following analysis showed that student engagement mediates the effect of socioeconomic status and student perception of teaching methods on technological, pedagogical, and content knowledge (TPACK) and global competence. Conclusion: Student perception about the lecturer teaching methods would increase global competence, and then increasing student engagement would ultimately be able to increase global competence as well. Keywords: socioeconomic status, student engagement, perception of teaching methods, technological pedagogical content knowledge, global competence.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202226